The Relationship of the Region’s Export Potential and the Start-Up Movement of the Youth - Glukhikh, Pavel Leonidovich; Myslyakova, Yuliya Gennadyevna; Malysheva, Vladimirovna; Krasnykh, Sergey Sergeevich (Economy of Regions, 2018)
Enhancing the role of entrepreneurship as an instrument of export diversification for sustainable development of the economy of the country and regions is a topical problem, The research is focused on the regional export potential including youth startups (small and medium enterprises, or SME), whose non-raw exports should increase by 1,5-2 times by 2020 according to the roadmap «Export» approved the Government of the Russian Federation The purpose of the article is to clarify theoretical and methodological foundations as well as to develop assessment methodology and appropriate recommendations on the enhancing the export potential of technology SME, As a hypothesis, we have suggested that there is a relationship between the regional export potential and the development of the start-up youth movement, The study used mathematical methods for processing statistical data, in particular, a correlation analysis of export statistics and start-up companies, The methodological tools were tested on the example of statistical data of 2016 for 39 regions of Russia, According to the correlation analysis, we have identified the direct moderate dependence between the specific weight of technologies export in the gross regional product (GRP) and the number of residents of business incubators in regions, In other words, the influence of the development of regional technology export on the number of existing startup companies is positive but moderate, This conclusion contributes to the solution of the task to ensure Russia’s status as a global technology leader by increasing a share of high-tech export, including SME and start-ups focused on export, The content analysis has shown that the emerging regional concepts and export development strategies give insufficient consideration to the export potential of SME, Therefore, we offer a set of measures to enhance this potential including organizational and coordination aspect of the export ecosystem, The results can serve as a guideline for developing mechanisms and instruments to promote the development of non-raw exports of technology SME to diversify the regional economy